Factors Associated with Glycemic Control Among Patients with Type 2 Diabetes at Chittagong Medical College Hospital (Journal of Chittagong Medical College Teachers' Association, 2022)
Background: Glycemic control is the main therapeutic goal for the prevention of diabetes related complications. However, achieving optimal glycemic control on long term basis among patients with Type 2 diabetes remains challenging in developing countries like Bangladesh. The purpose of the study to determine the factors associated with glycemic control among patients with Type 2 diabetes at Chittagong Medical College Hospital, Chattogram, Bangladesh.  Materials and methods: This cross sectional study included 120 patients with Type 2 diabetes aged 40-75 years who attended at Outpatient Department of Endocrinology, Chittagong Medical College Hospital between July 2020 to June 2021. Important variables in this study were socio-demographics, fasting blood glucose, HbA1c, BMI, waist circumference, duration of DM, proteinuria and documented history of chronic complications. Patent’s HbA1c were categorized into good glycemic control